2022
DOI: 10.1109/tap.2022.3140528
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Thin Artificial Magnetic Conductor for Gain Enhancement of Antenna-on-Chip

Abstract: System-on-Chip (SoC) has become an attractive solution to achieve highly integrated wireless systems. However, the Antenna-on-Chip (AoC) suffers from poor radiation due to the lossy silicon substrate in standard CMOS processes. Artificial Magnetic Conductors (AMC) with the ground plane above the silicon can enhance the radiation, however, fitting the AMC completely in the thin stack-up (~10-15 μm) is extremely challenging, particularly for frequencies below 100 GHz. In this paper, Metallic Posts (MP) and Embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…This configuration has previously only been possible with a thick dielectric layer [23], which is not suitable for conventional CMOS processes. In our previous work, we showed that a specially designed thickness reduction structure (TRS) could reduce the AMC thickness by 41% [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This configuration has previously only been possible with a thick dielectric layer [23], which is not suitable for conventional CMOS processes. In our previous work, we showed that a specially designed thickness reduction structure (TRS) could reduce the AMC thickness by 41% [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the thickness issue that was tackled in [24], the ineffective illumination of the AMC by AoC is another essential issue that affects the performance of the AMC and antenna combination significantly. Theoretically, the AMC must be an infinitely large periodic surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…can provide an improved end-user experience with enhanced 29 coverage and spectral efficiency. Therefore, numerous studies 30 have been conducted on mmWave beamforming systems [1], 31 [2], [3], [4], [5], [6], [7], [8], [9], [10], [11]. 32 However, the coverage hole problem in a non-line-of-33 sight (NLOS) environment remains difficult to solve, even 34 with the advanced beamforming technologies of 5G FR2 35 bands, as explained below.…”
Section: Introductionmentioning
confidence: 99%
“…However, this beam pattern is impractical because it represents an ideal rectangular beam, which assumes that the antenna radiates equally in the rectangular area. In [49], the beam efficiency is applied in (7) to calculate the practical case, as…”
mentioning
confidence: 99%